Discovery and Optimization of a Series of 2-Aryl-4-Amino-5-(3′,4′,5′-trimethoxybenzoyl)Thiazoles as Novel Anticancer Agents - Romagnoli, Romeo (2012)
[Image: see text] A new series of tubulin polymerization inhibitors based on the 2-aryl/heteroaryl-4-amino-5-(3′,4′,5′-trimethoxybenzoyl)thiazole scaffold was synthesized and evaluated for growth inhibition activity on a panel of cancer cell lines, cell cycle effects, and in vivo potency. Structure–activity relationships were elucidated with various substitutions at the 2-position of the thiazole skeleton. Hydrophobic moieties, such as phenyl and 3-thienyl, were well tolerated at this position, and variation of the phenyl substituents had remarkable effects on potency. The most active compound (3b) induced apoptosis through the mitochondrial pathway with activation of caspase-3. We also showed that it has potential antivascular activity since it reduced in vitro endothelial cell migration and disrupted capillary-like tube formation at noncytotoxic concentrations. Furthermore, compound 3b significantly reduced the growth of the HT-29 xenograft in a nude mouse model, suggesting that 3b is a promising new antimitotic agent with clinical potential.